The Experience of Professional Burnout: The Perspective of Practicing Psychotherapists - Momgaudytė, Elzė; Vaštakė, Marija (Psichologija, 2025)
The article presents the phenomenon of professional burnout among practicing psychotherapists, which is an extremely relevant issue that, surprisingly, has been underexplored by using qualitative methods in scientific literature. Interestingly, while professional burnout among psychotherapists has been extensively studied quantitatively, there is a lack of systematic qualitative research and meta-analyses addressing how psychotherapists experience professional burnout (Vivolo et al., 2024). The aim of this study is to understand and describe psychotherapists’ experiences of professional burnout. The study involved five psychotherapists who had experienced burnout during their psychotherapeutic practice, aged between 31 and 47 years (M = 40). A qualitative research strategy was chosen, with data collected through semi-structured interviews and processed by using thematic analysis (Braun & Clarke, 2021). The findings mostly align with some existing literature on psychotherapist burnout; however, additionally, the data have revealed that many of the burnout prevention measures identified in the literature often remain unimplemented in practice, while help-seeking stigma and job-specific challenges frequently go unaddressed in psychotherapists’ everyday work context. Four main themes emerged in the study regarding the experience of professional burnout among psychotherapists: 1) A gradual journey toward burnout; 2) A work culture that fosters burnout; 3) Burnout and personality: being more than just a psychotherapist; 4) The significance of job-specific factors in burnout. These themes not only illustrate how psychotherapists experience the phenomenon of professional burnout but also highlight both external and internal factors influencing its manifestation. External factors include working conditions, peer support, and job characteristics, while internal factors encompass the psychotherapists’ personality traits, ability to set boundaries, personal goals and standards, and attention to their own needs.
Keywords: professional burnout; psychotherapy; psychotherapist burnout